Effects of human disturbance on the behavior and energetics of nonbreeding sanderlings - Morton, John M. (Virginia Tech, 1996)
Human disturbance of avifauna and other wildlife is defined as any intentional or unintentional anthropogenic action that elicits a metabolic or behavioral response. I proposed that the energetic response to disturbance should be reflected as increased existence metabolism (EM). If so, then there must be three behavioral responses to increased EM: increased energy intake compensates for increased EM, habituation reduces increased EM, and dispersal avoids increasing EM altogether. I applied this model to captive and free-ranging nonbreeding sanderlings (Calidris alba). I exposed 24 captive sanderlings to a 5-min disturbance event during each of 10 diurnal hours over two 4-d trials. The metabolizable energy of food ingested was determined for each bird daily. Total body electrical conductivity and body mass were measured during trials to account for energy derived from metabolized body tissues. These combined values suggest that EM was elevated by 7% in response to disturbance during 8% of daylight hours. Caged sanderlings responded to disturbance with alert and attempted escape behaviors; i.e., dispersal. Sanderlings spent more time attempting to escape on the first day of each trial and during the first of 10 disturbance events in a day, suggesting some behavioral habituation. There was evidence of compensatory feeding after the trials, but not during them. Abundance, behavior, and distribution of free-ranging sanderlings were studied at Assateague Island National Seashore, Maryland, during two winters in 1991-93. Increasing pedestrian traffic decreased the probability of sanderling occurrence on 200-m plots by as much as 45%. Average sanderlings ambulated or flushed when pedestrians and vehicles approached within 20 m and 10 m, respectively, and flushed more frequently in response to pedestrians than vehicles. Mean densities were nearly 60% less on disturbed than undisturbed 200-m plots. Sanderling densities were highest on plots with invertebrate prey and no disturbance, and lowest on those with disturbance ...